Analysis of the Tempering Process Results with Temperature Variations on the Mechanical Properties of AISI 4340 Material Hardness - Jordy Giano; Risal Abu; Mukhnizar Mukhnizar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of tempering temperature variations on the hardness of AISI 4340 steel after undergoing a quenching process. AISI 4340 is a high-strength low-alloy steel widely used in manufacturing industries, making the control of its mechanical properties through heat treatment crucial. In this study, the steel specimens were initially heated to 800°C and rapidly cooled (quenched) in water. Subsequently, the specimens were subjected to tempering at three different temperatures—200°C, 400°C, and 600°C—with a holding time of 60 minutes. The mechanical properties were evaluated using the Rockwell hardness test (HRC scale) with three measurement points on each specimen. The results indicate that variations in tempering temperature significantly affect the hardness of the steel. Tempering at 200°C produced the highest hardness value of 22.00 HRC due to the presence of tempered martensite with fine carbide precipitation. At 400°C, the hardness decreased to 15.90 HRC, attributed to the transformation of martensite into ferrite and fine cementite (troostite). Meanwhile, tempering at 600°C resulted in a hardness value of 17.80 HRC, characterized by a more stable and ductile sorbite structure. Overall, the findings show that increasing tempering temperature generally decreases hardness while enhancing the ductility of AISI 4340 steel.